Strategi Diplomasi Publik Jerman pada UEFA EURO 2024 - Mochammad Habibie Purnomo Putra; Costantine Badrani Mongide; Berlianto Juan; Ario Bimo Utomo (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study analyzes Germany's public diplomacy strategy in organizing UEFA EURO 2024 as a Mega Sporting Event (MSE) to build a positive image in the eyes of the international community. Using Mark Leonard's (2002) public diplomacy theory, this study highlights three main dimensions: News Management, Strategic Communications, and Relationship Building. A qualitative approach is used with secondary data from UEFA's official website, media, and relevant literature. In the News Management aspect, Germany utilizes the International Broadcast Center (IBC) in Leipzig to control the global narrative. IBC broadcasts matches to more than 200 countries and promotes German culture and tourism through UEFA's official platforms and broadcasting partners. In Strategic Communications, Germany builds a national identity through the slogan Vereint im Herzen Europas, the official song Fire, colorful logos representing the 24 participating countries, the #LightYourFire campaign, and the Albärt mascot depicting inclusivity and tolerance. Meanwhile, Relationship Building was realized through the recruitment of 16,000 volunteers from 124 countries, the holding of FAN Festivals in 10 cities that attracted 5.8 million visitors, and the Instagram account @unitedbyfootball2024 as a medium of interaction. These efforts strengthened international relations through direct interaction, training, cultural exchange, and media involvement. This study concluded that Germany successfully utilized EURO 2024 as a means of public diplomacy by synergistically integrating the three dimensions to create a positive national image on the global stage.